PENGARUH PEMAHAMAN PERATURAN PAJAK, SANKSI PERPAJAKAN, PEMERIKSAAN PAJAK TERHADAP KEPATUHAN WAJIB PAJAK ORANG PRIBADI (WPOP) - Asterina, Fenty; Septiani, Chessy (Balance : Jurnal Akuntansi dan Bisnis, 2019)
This research was made to answer the problem formulation in this study that was to find out whether there were effects of tax regulation understanding, tax sanctions and tax audits on individual taxpayer compliance. With the aim of research was to determine the effect of tax regulations on individual taxpayer compliancein KPP Pratama Palembang SeberangUlu, to determine the effect of tax sanctions on individual taxpayer compliance in KPP Pratama Palembang Seberang Ulu. The variables in this study were tax regulations understanding (X1), taxation sanctions (X2), taxpayer compliance (Y). this type of research was associative and descriptive. The population in this study was 45 UKM Seberang Ulu I. Data that used in this research primary data of questionnaire. The data analysis technique used is multiple linear regression with the help of SPSS version 22.The results of the study showed that taxregulations understanding did not have an effect and was not significant on taxpayer compkiance, while taxation sanctions and tax audits had a positive effect on taxpayer compliance.